A New Efficient Method for Information Security in Hadoop - Shadan Muhammed Jihad Abdalwahid; Banar Fareed Ibrahim; Sami Hassan Ismael; Shahab Wahhab Kareem (QALAAI ZANIST JOURNAL, 2022)
A significant difficulty in developing a specialized Hadoop for cloud computing, and to tackle this problem, an anticipated safe cloud computing system has been built. Hadoop was utilized in this field to develop and improve the security of handling and gathering data from users. Other Apache Big Data technologies include Hadoop, which uses the Map-Reduce architecture to prepare enormous amounts of data. Hadoop is one of the most significant tools for dealing with Big Data issues. Data storage security is one of the most challenging tasks, and the Hadoop distributed file system (HDFS) lacks a well-defined security policy. The proposed technique encrypts all of the files stored in HDFS with public-key cryptography to safeguard them all. The acquired data is encrypted in HDFS during the data collecting process using the proposed data encryption method (Rabin RZ). The proposed method is compared to the Paillier method and the default Rivest–Shamir–Adleman (RSA) cryptosystem, respectively. When compared to other cryptosystems, the proposed method has a more powerful computational complexity and a smaller latency than the alternatives.